Automation of an African wooden pestle: pneumatic or hydraulic actuation? - Ella Eny, Gérémino; Angue Mintsa, Honorine; Joseph Oyobé Okassa , Aimé; Luthenda, Gamany (International Journal of Engineering and Technology, 2023)
This paper investigates the automation of an African wooden pestle. This device is used in the kitchen to cook traditional African meals. Because pounding food is painful for the human arm and food blenders cause a lack of consistency in the final product, we study the automation of this device by proposing two solutions. The first solution is the closed-loop electro-hydraulic linear actuation. The second solution is the closed-loop electro-pneumatic linear actuation. These two actuators are chosen because they generate a translational force. A particular reference signal is proposed to mimic the pounding process. The numerical simulations executed in the Matlab/ Simulink/ Simscape environment reveal that the hydraulic actuation provides the best results, particularly for products with medium-high mechanical resistance. Future works will present the results obtained with experimental prototypes.